press Coverage Of Youth Social Problems An analytical Study of Al- Sabah Newspaper - Ali, Yousra Hamza; Al-Sarrag, Shukriya hKokaz (ALBAHITH ALALAMI, 2019)
The tremendous political transformations that took place in Iraq after 2003 led by the USA and its allies led to a change of its political system under the slogan of liberating Iraq from dictatorship, establishing a democratic system and spreading freedom among members of the society.However, democracy was a mantle under which the US intended to achieve its expansionist ambitions in the region. It did not come to liberate Iraq as it claimed, but it occupied Iraq and all its materialistic and human resources. Thus, this change resulted in lots of negative events and societal pests that affected the entire social system and values. Youth is an important segment; it is one of the most affected age groups with the happenings and accidents around. Iraq is considered as one of the youngest communities having (9.2) million people according to the results of enumeration and numbering of the Central Bureau of Statistics, and rose slightly to (9.3) million in 2011. The absence and deterioration of the security and the political situation led to the creation of a state of chaos and looting, destruction of public property, emigration, sectarian conflict , tribal appearance, increasing divorce rates , as well as widespread of administrative and financial corruption among the political class. All this resulted in the spread of poverty and unemployment and the migration of capital (finances) seeking for a safe environment to live in. Hence, it was essential to shed lights on those problems , Youth and how to direct and guide them in a proper way. Media in general and the press in particular are regarded one of the social adjustment institutions via their roles on their societies. These institutions have been regarded the third institution of social development coming after family and school. Moreover, they monitor and reform society as a whole. So that this study sheds light on the various problems, issues and challenges that face the Iraqi society, in an attempt to identify their causes and trying to find suitable solutions, so as to keep Youth, being the real wealth, safe and rehabilitate them after the great collapse that has damaged their values and customs. By doing so, Youth are offered the best opportunities for good life making in order to make them more productive and active enjoying stability leading to adapt their national identity.This study adopts the social problems of the Youth. Those problems are danger and have bad effect on the Youth as they lead to psychological diseases that generate depression and lack of self-interest. The research sheds light on these problems trying to find appropriate solutions that can contribute to reduce and restrict those problems that gnawed Iraq.The research aims at identifying the reality of the Iraqi press through various aspects of press coverage of the social problems of the Youth in Al- Sabah newspaper for the period between (1-1-2017 and 31-3-2017). Some of the goals of this study are : 1-Identify the most prominent problems facing young people, which received attention (Al-Sabah newspaper). 2-stand on the most prominent arts journalism that dealt with the problems of young people in (Sabah newspaper) ..3-Detection of the types of coverage that dealt with the problems of young people (Al - Sabah newspaper).The research reached the following results: 1-The most prominent problems faced by young people in the Iraqi press are the political problems. They came in Al-Sabah newspaper with a percentage of 31.94%, which is superior to the rest of the problems of other youth because of its aggravation and control over all aspects of life.2-The journalistic arts, which dealt with the problems of young people in the Iraqi press (the subject of research), were ranked first in Al-Sabah newspaper by 39.85%. It came ahead of the rest of the other press arts, focusing on press columns dealing with youth problems,View more space.3-The coverage of the problems of young people based on analysis and interpretation in Al-Sabah newspaper increased by (54.80%) compared to the rest of the coverage of the other press, depending on the art of the column in the coverage of the coverage of youth problems.